Spatial Difference of Interactive Effect Between Temperature and Daylength on Ginkgo Budburst - Wu, Zhaofei; Wang, Shuxin; Fu, Yongshuo H.; Gong, Yufeng; Lin, Chen-Feng; Zhao, Yun-Peng; Prevéy, Janet S.; Zohner, Constantin (Frontiers in Plant Science, 2022)
Climate warming-induced shifts in spring phenology have substantially affected the structure and function of terrestrial ecosystems and global biogeochemical cycles. Spring phenology is primarily triggered by spring temperature and is also affected by daylength and winter chilling, yet the relative importance of these cues across spatial gradients remains poorly understood. Here we conducted a manipulative experiment with two daylength and three temperature treatments to investigate spatial differences in the response of ginkgo budburst to temperature and daylength, using twigs collected at three sites across a spatial gradient: a control site at a low latitude and low elevation on Tianmu Mountain (TMlow), a low latitude and high elevation site on Tianmu Mountain (TMhigh), and a high latitude site on Jiufeng mountain (JF). The mechanisms were also tested using in situ phenological observations of ginkgo along latitudes in China. We found that, compared to TMlow individuals, budburst dates occurred 12.6 (JF) and 7.7 (TMhigh) days earlier in high-latitude and high-elevation individuals when exposed to the same temperature and daylength treatments. Importantly, daylength only affected budburst at low latitudes, with long days (16 hours) advancing budburst in low-latitude individuals by, on average, 8.1 days relative to short day (8 hours) conditions. This advance was most pronounced in low elevation/latitude individuals (TMlow = 9.6 days; TMhigh = 6.7 days; JF = 1.6 days). In addition, we found that the temperature sensitivity of budburst decreased from 3.4 to 2.4 days ℃-1 along latitude and from 3.4 to 2.5 days ℃-1 along elevation, respectively. The field phenological observations verified the experimental results. Our findings provide empirical evidence of spatial differences in the relative effects of spring temperature and daylength on ginkgo budburst, which improved our understanding of spatial difference in phenological changes and the responses of terrestrial ecosystem to climate change.